2019
DOI: 10.1096/fj.201800980rr
|View full text |Cite
|
Sign up to set email alerts
|

C5a receptors C5aR1 and C5aR2 mediate opposing pathologies in a mouse model of melanoma

Abstract: The canonical complement component 5a (C5a) receptor (C5aR) 1 has well‐described roles in tumorigenesis but the contribution of the second receptor, C5aR2, is unclear. The present study demonstrates that B16.F0 melanoma cells express mRNA for both C5aR1 and C5aR2 and signal through ERK and p38 MAPKs in response to C5a. Despite this, C5a had no impact on melanoma cell proliferation or migration in vitro. In vivo studies demonstrated that the growth of B16.F0 melanoma tumors was increased in C5aR2–/– mice but re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 63 publications
1
12
0
Order By: Relevance
“…However, C5aR2 instead displays a pro-inflammatory role in several autoimmune diseases, resulting in an enigmatic and controversial role 41 . In consistent with a previous report in a melanoma bearing murine model 42 , we showed that in contrast to C5aR1, C5aR2 deficiency accelerated tumor development, suggesting an anti-inflammatory role of C5aR2 in AOM/DSS-induced CRC tumorigenesis. The result may also explain the observation that tumor burden in C5- deficient mice is greater than in C5ar1- deficient mice.…”
Section: Discussionsupporting
confidence: 93%
“…However, C5aR2 instead displays a pro-inflammatory role in several autoimmune diseases, resulting in an enigmatic and controversial role 41 . In consistent with a previous report in a melanoma bearing murine model 42 , we showed that in contrast to C5aR1, C5aR2 deficiency accelerated tumor development, suggesting an anti-inflammatory role of C5aR2 in AOM/DSS-induced CRC tumorigenesis. The result may also explain the observation that tumor burden in C5- deficient mice is greater than in C5ar1- deficient mice.…”
Section: Discussionsupporting
confidence: 93%
“…C5a can interact with two different receptors, C5aR1 and C5aR2, with opposite functions. C5aR1 seems to have pro-tumoral role, whereas C5aR2 has more limited impact but tends to modulate the tumor growth [14].…”
Section: Therapeutic Inhibition Of C5ar1 On Tumor Cells Versus On Immmentioning
confidence: 95%
“…Anaphylatoxins (C3a and C5a) are released in the circulation and have an important role to induce inflammation and activate cells expressing anaphylatoxin receptors (C3aR, C5aR1/C5aR2). C5aR1 and C5aR2 seem to have opposite effects, especially in the tumor context [14]. MAC formed by the association of C5b molecule with C6 that acquire the ability to interact with lipid bilayer, the C7 and C8 molecules bind C5b and insert into lipid bilayer, then several molecules of C9 polymerize creating the lytic pore, causing membrane permeabilization, cell activation and/or the cell death [15].…”
Section: Complement Effector Pathwaysmentioning
confidence: 99%
“…Over the last few years, evidence has indicated that C5a activation triggers a cascade of events that are involved in the pathophysiology of PN and in the genesis of painful states of neuro-inflammation [8]. C5a exerts its biological functions by binding two receptors, C5a receptor-like 1 (C5aR1, also referred to as CD88), a class A seven-transmembrane Gprotein-coupled receptor (GPCR), and C5a receptor-like 2 (C5aR2, also known as C5L2 or GPR77) [33], a homolog of C5aR1, but which is not coupled to intracellular heterotrimeric G-proteins due to a mutation in G-protein recognition sequence. C5aR1 is expressed by a broad range of cell types, including all cells of myeloid origin (neutrophils, eosinophils, monocytes, macrophages, dendritic cells, mast cells), lymphocytes, and non-myeloid cells, such as lung, liver, kidney, skin, and central nervous system (CNS) cells [5,34].…”
Section: Peripheral Neuropathies and C5a/c5ar1 Axismentioning
confidence: 99%